Phenotyping Adopters of Mobile Applications Among Patients With COPD: A Cross-Sectional Study - Flora, Sofia; Hipólito, Nádia; Brooks, Dina; Marques, Alda; Morais, Nuno; Silva, Cândida G.; Silva, Fernando; Ribeiro, José; Caceiro, Rúben; Carreira, Bruno P.; Burtin, Chris; Pimenta, Sara; et al. (Frontiers in Rehabilitation Sciences, 2021)
Effectiveness of technology-based interventions to improve physical activity (PA) in people with COPD is controversial. Mixed results may be due to participants’ characteristics influencing their use of and engagement with mobile health apps. This study compared demographic, clinical, physical and PA characteristics of patients with COPD using and not using mobile apps in daily life. Patients with COPD who used smartphones were asked about their sociodemographic and clinic characteristics, PA habits and use of mobile apps (general and PA-related). Participants performed a six-minute walk test (6MWT), gait speed test and wore an accelerometer for 7 days. Data were compared between participants using (App Users) and not using (Non-App Users) mobile apps. A sub-analysis was conducted comparing characteristics of PA–App Users and Non-Users. 59 participants were enrolled (73% male; 66.3±8.3yrs; FEV1 48.7±18.4%predicted): 59% were App Users and 25% were PA-App Users. Significant differences between App Users and Non-App Users were found for age (64.2±8.9 vs. 69.2±6.3yrs), 6MWT (462.9±91.7 vs. 414.9±82.3m), gait speed (median 1.5 [Q1─Q3: 1.4─1.8] vs. 2.0 [1.0─1.5]m/s), time in vigorous PA (0.6 [0.2─2.8] vs. 0.14 [0.1─0.7]min) and self-reported PA (4.0 [1.0─4.0] vs. 1.0 [0.0─4.0] points). Differences between PA–App Users and Non-Users were found in time in sedentary behavior (764.1 [641.8─819.8] vs. 672.2 [581.2─749.4] min) and self-reported PA (4.0 [2.0─6.0] vs. 2.0 [0.0─4.0] points). People with COPD using mobile apps were younger and had higher physical capacity than their peers not using mobile apps. PA-App Users spent more time in sedentary behaviors than Non-Users although self-reporting more time in PA.